The construction of solidarity at school: the virtues, the reason, and the affectivity (Educação e Pesquisa, 2006)
Discussing how people can build up solidarity, and drawing from psychological assumptions that guarantee that such virtue is constructed by each one in their interaction with the environment, this research points to a path for the formation of more autonomous and solidary subjects: the cooperation as a strategy to conceive the construction of virtues. To this end, a comparative investigation was made of the judgments of children of both sexes, aged 6 and 7, in two kinds of environments: A - based on authoritarian relations; and B - in relationships of cooperation. Diagnostic tests for Jean Piaget's operatory behavior were used to investigate the parallel between the cognitive and moral structures of the subjects. The study also used the observation of the interpersonal relationships and the discussion of moral dilemmas split into two groups, and which fulfilled two conditions: to inspect the judgment of solidarity between peers, and in the presence of authority. Results demonstrate the existence of an evolution in the disposition of the subjects to be solidary, linked to the prospect of significant experiences of solidarity and mutual respect, characteristic of a cooperative environment. Such results allow us to envisage a "Pedagogy of Virtues" that takes in the development of cognitive structures and affective aspects to the construction of moral personalities.